2040: climate change documentary analysis - Louey, Taylor R.; Eng, Alena; Hang, Jimmy; Kaur, Jaismeen; Nixon, Katelyn; Sperling, Katlynn (My University, 2025)
This paper examines the impacts of climate change on human health and well-being, utilizing insights from the documentary 2040, directed by David Gameau. It explores how agriculture and ocean ecosystems can contribute to climate change mitigation. While the agricultural industry is a significant source of emissions, it is also particularly vulnerable to climate impacts (Gameau, 2019). Rising ocean temperatures and acidification threaten biodiversity and disrupt vital ocean circulation (Gameau, 2019). This paper highlights the interrelation of climate change, planetary health, and human well-being and advocates for a multisectoral approach. It emphasizes strategies like sustainable agriculture and marine permaculture alongside adaptation measures to reduce vulnerability. This research accentuates the importance of environmental justice and the need for equitable and inclusive climate action. Through examination of the United Nations Sustainable Development Goals (SDGs), such as zero hunger and responsible consumption, this paper identifies crucial intervention areas. Recommendations include reducing waste, promoting sustainable consumption, and implementing upstream policies to support climate mitigation. The research highlights the urgent need for global action to combat climate change and protect human health for future generations. Given the climate crisis's implications for nursing practice, adopting planetary nursing approaches is essential to safeguard both the planet and its population.
Keywords: climate change; human health; United Nations Sustainable Development Goals (SDGs); planetary nursing approaches; environmental justice; documentary analysis; 2040 documentary